2014
DOI: 10.1016/j.taap.2013.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of changes in hepatic gene expression in a murine model of tolerance to acetaminophen hepatotoxicity (autoprotection)

Abstract: Pretreatment of mice with a low hepatotoxic dose of acetaminophen (APAP) results in resistance to a subsequent, higher dose of APAP. This mouse model, termed APAP autoprotection was used here to identify differentially expressed genes and cellular pathways that could contribute to this development of resistance to hepatotoxicity. Male C57BL/6J mice were pretreated with APAP (400 mg/kg) and then challenged 48 hr later with 600 mg APAP/kg. Livers were obtained 4 or 24 hr later and total hepatic RNA was isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…A recent gene array analysis performed in our laboratory also demonstrated Fmo3 gene induction in the APAP autoprotection mouse model (mice receiving a low hepatotoxic APAP dose that become resistant to a subsequent higher APAP dose)(O'Connor et al, 2014). Unlike with AhR agonists that result in marginal increases in Fmo3 protein expression in mouse liver, we showed significant increases in Fmo3 protein levels by 15-fold in APAP autoprotectedmice(Rudraiah et al, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…A recent gene array analysis performed in our laboratory also demonstrated Fmo3 gene induction in the APAP autoprotection mouse model (mice receiving a low hepatotoxic APAP dose that become resistant to a subsequent higher APAP dose)(O'Connor et al, 2014). Unlike with AhR agonists that result in marginal increases in Fmo3 protein expression in mouse liver, we showed significant increases in Fmo3 protein levels by 15-fold in APAP autoprotectedmice(Rudraiah et al, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…This observation is in agreement with a recent finding by Leiser et al , who demonstrated that FMO enzymes increase the lifespan and enhance proteostasis in nematodes undergoing a hypoxic response, which is another form of stress/cytotoxicity 31 . It is intriguing that FMO3, once considered to be non-inducible by xenobiotic treatment, has been shown not only to be inducible by our group and others 12, 13, 32, 33 but also to protect against APAP-induced cytotoxicity in hepatocytes 13 . This highlights the evolving nature of our understanding about FMO3 function, which calls for more mechanistic studies to delineate FMO3’s role in protecting against APAP hepatotoxicity.…”
Section: Gene Expression and Proteome Profiling In Autoprotection/hetmentioning
confidence: 88%
“…It is intriguing and worth noting that a similar shift in localization of flavin-containing monooxygenase-3 (FMO3) was also noted in livers of our APAP autoprotection model 13 . Fmo3 was identified from a microarray study as a potential gene contributing to resistance to liver toxicity in our APAP autoprotection mouse model 12 . Similar to CYP450s, FMO3 is a phase 1 drug-metabolizing enzyme involved in the oxygenation of nitrogen- and sulfur-containing endogenous substrates (such as cysteamine, trimethylamine, etc.)…”
Section: Autoprotection and Heteroprotectionmentioning
confidence: 99%
See 2 more Smart Citations